2001
DOI: 10.1093/qjmed/94.8.429
|View full text |Cite
|
Sign up to set email alerts
|

Asthma admissions and thunderstorms: a study of pollen, fungal spores, rainfall, and ozone

Abstract: Asthma admissions have been reported to increase during thunderstorms. In some cases, this has been attributed to rises in pollen or fungal spore counts occurring alone or in combination with rainfall. We tested the hypothesis that thunderstorms in general are associated with asthma admissions, and investigated the possible roles of pollen, fungal spores, ozone, and other meteorological factors. We obtained data on multiple pollen and fungal spore counts, rainfall, temperature, ambient ozone concentrations, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 19 publications
1
47
0
1
Order By: Relevance
“…In neither study were there adequate data on environmental levels of grass pollen or fungal spores at the time of the asthma outbreak. Ozone causes bronchial hyperresponsiveness, 27 and levels of ozone were very high before the thunderstorm on July 29. Taylor and Jonsson 28 have proposed a mechanism by which updraughts entrain pollen grains into the high humidity of a cloud base, where the grains rupture, and downdraughts transport the fragments to ground level in dry cold outflows extending about 5 km ahead of the rainfall.…”
Section: Discussionmentioning
confidence: 99%
“…In neither study were there adequate data on environmental levels of grass pollen or fungal spores at the time of the asthma outbreak. Ozone causes bronchial hyperresponsiveness, 27 and levels of ozone were very high before the thunderstorm on July 29. Taylor and Jonsson 28 have proposed a mechanism by which updraughts entrain pollen grains into the high humidity of a cloud base, where the grains rupture, and downdraughts transport the fragments to ground level in dry cold outflows extending about 5 km ahead of the rainfall.…”
Section: Discussionmentioning
confidence: 99%
“…68,69 The interesting observation that increased asthma admissions were associated with thunderstorms was originally attributed to peak fungal spore counts preceding or during the weather front but not to concomitant increases in air pollutants. [70][71][72][73][74] Several more recent studies failed to show an association with thunderstorms but instead found a positive association between asthma admissions and higher levels of ozone at these times. As previously discussed, controlled challenge studies all have demonstrated that inhaled ozone, NO 2 , and SO 2 , individually or in combination, might enhance the airway response to inhaled allergens, thereby inducing asthma exacerbations.…”
Section: Interaction Between Allergen and Pollutantsmentioning
confidence: 99%
“…Bioaerosols are abundant in nature, especially fungi and pollen (Macher, 1999;Monn and Koren, 1999;Jones and Harrison, 2004). The associations between exposure to ambient bioaerosols and adverse health effects, such as exacerbation of asthma, allergies, and respiratory diseases, have been reported (Anderson et al, 2001;Burge, 2001;Burge and Rogers, 2000;Cakmak et al, 2002;Peden and Reed, 2010).…”
Section: Introductionmentioning
confidence: 99%